Geographical Information System Complaints on Damage to Roads and Bridges in Semarang City - Stefanus Lintang Timur Aji Pamungkas; Albertus Dwiyoga Widiantoro; Hendra Prasetya (Soegijapranata Catholic University, 2021)
In a world that has developed towards digital, especially in the field of information and communication technology. Using technology is very useful in easing human work. In managing information on damage to roads and bridges in Semarang City, it can be facilitated by visual representation.Processing in the form of maps using leafletjs is a lightweight and easy to use javascript framework, the advantage of leafletjs is that there are many third parties that are easy to add to the main function of the leafletjs framework. After making an application it will distribute 30 questionnaires to the general public so that an application that is easy to use in the long term can be obtained.